Pineapples - Bassier, Emma (2021)
This book introduces readers to how pineapples are grown, harvested, and prepared. Features include a table of contents, fun facts, infographics, Making Connections questions, a glossary, and an index. QR Codes in the book give readers access to book-specific resources to further their learning.
"4D book!"--Cover.
Includes index.
Ages 4-7
Keywords: Pineapple -- Juvenile literature